A Carrier Class IoT Service Architecture Integrating IMS with SWE. (22nd May 2014) - Xie, Dongliang; Shang, Chao; Chen, Jinchao; Lai, Yongfang; Pang, Chuanxiao
Abstract : Integrating the sensing capabilities of wireless sensor network (WSN) into the traditional telecom network is an important stage to realize future ubiquitous intelligence in the Internet of Things. Driven by the vision of service oriented architecture (SOA), this paper proposed a carrier class Internet of Things (IoT) service architecture named as MUSE. MUSE integrates WSN with IMS OSE framework to enable the WSN services to be operable and manageable. Also sensor web enablement (SWE) framework is adopted to shield the heterogeneity of different WSNs. MUSE consists of two key entities—MUSE Enabler and MUSE Gateway. On the one hand, the architecture promotes the node manageability and enriches the diversity of high level task planning flexibility. On the other hand, the architecture extends the telecom context-aware service and realizes service operability and network scalability. Moreover, the key components of the architecture and the detailed service procedure were introduced in the paper. Besides, an intelligent building prototype with 20 nodes was illustrated and the feasibility and performance of MUSE were verified at last.